Gal-3 Deficiency Suppresses Novosphyngobium aromaticivorans Inflammasome Activation and IL-17 Driven Autoimmune Cholangitis in Mice - Arsenijevic, Aleksandar; Milovanovic, Jelena; Stojanovic, Bojana; Djordjevic, Dragana; Stanojevic, Ivan; Jankovic, Nenad; Vojvodic, Danilo; Arsenijevic, Nebojsa; Lukic, Miodrag L.; Milovanovic, Marija (Frontiers in Immunology, 2019)
Gal-3 has the role in multiple inflammatory pathways. Multiple-hit etiology of primary biliary cholangitis (PBC) and evolving immune response at various stages of the disease includes involvement of Gal-3 in PBC pathogenesis. In this study we aimed to clarify the role of Gal-3 in Novosphingobium aromaticivorans (N. aromaticivorans) induced biliary disease. Autoimmune cholangitis was induced in mice by two intraperitoneal injections of N. aromaticivorans within two weeks. The role of Gal-3 was evaluated by using Lgals3−/− mice and mice treated with Gal-3 inhibitor. The histological and serological parametars of disease, phenotype of dendritic, NK, NKT and T cells and inflammasome expression were evaluated. Marked attenuation of the disease in Lgals3−/− and Gal-3 inhibitor, DAVANAT®, treated mice is manifested by the absence of bile duct damage, granulomas and fibrosis. Liver infiltrates of N. aromaticivorans infected wild type mice had higher incidence of proinflammatory macrophages, dendritic cells, NK, NKT and T cells. Lgals3 deletion and treatment with Gal-3 inhibitor reduced inflammatory mononuclear cell infiltrate, expression of NLRP3 inflammasome in the liver infiltrates and interleukin-1β (IL-1β) production in the livers of N. aromaticivorans infected mice. In vitro stimulation of wild type peritoneal macrophages with N. aromaticivorans caused increased NLRP3 expression, caspase-1 activity and IL-1β production compared with Lgals3-/- cells. Our data highlight the importance of Gal-3 in promotion of inflammation in N. aromaticivorans induced PBC by enhancing the activation of NLRP3 inflammasome and production of IL-1β and indicate Gal-3 as possible therapeutical target in autoimmune cholangitis. Galectin-3 appears involved in inflammatory response to gut commensal leading to PBC.